(untitled) (Revista cientifica In Vestigium Ire, 2019)
his paper analyzes the socioeconomic factors that influence the inhabitants ofTunja to belong to the informal sector; using as a source of information the Great lntegrated Household Survey (GEIH), conducted by the National Department of Statistics (DANE) during the years 2008 and 2015. Far this, a logit econometric model was carried out, which showed that the probability of being informal in Tunja decreases if it is male, if it has more years of schooling, and if it is occupied in the sectors of electricity, financial intermediation, real estate-rental activities -business, public, education and services. In addition to this, particular cases were analyzed, and it was observed how probable it is far a certain person (according to their years of schooling, their income and their gender) to belong to the informal sector.